Webcast technology in teaching: It’s implementation from the perspective of instructors - Md Yunus, Aida Suraya; Napis, Suhaimi; Kasa, Zakaria; Asmuni, Azizan; Abu Samah, Bahaman (Eurojournals, 2009)
The paper reports issues relating to the use of three modes of webcast technology in the teaching of two undergraduate courses, namely, BTK4003 (Bioinformatics) for Bachelor of Science (Biotechnology) programme at the Faculty of Food Science and Biotechnology, and DCE 3301 (Learning at Workplace) for Bachelor of Science (Human Resource Development) programme at the Faculty of Educational Studies at the Universiti Putra Malaysia. The study, aimed in determining the effectiveness of using webcast technology at the university was carried out in two phases over a period of two successive academic sessions. This report focuses on the experiences and perceptions of the observers who were instructors of the two courses. Lectures were conducted via three different modes of webcasting: i) Live streaming; ii) Pre-recorded streaming; and iii) Video-on-demand. The fourth group, which is the control group received live face-to-face normal lecture. Observations noted by instructors during the actual exercise were reported back to the research team to be compiled throughout the duration of the study. Findings show that experiences relayed by instructors who participated in the study ranged from the instructors’ state of readiness to be involved in the study to the management of students’ behaviour and the quality of network and connectivity. Lessons learned throughout the course of the study as well as some recommendations on best-practises are discussed.